Analisis Shopee Live Streaming Features, Collaboration Branding, Brand Ambassador, dan Kepercayaan terhadap Keputusan Pembelian pada Aplikasi E-Commerce Shopee (Studi Kasus Gen Z Surabaya) - Brandon, I Putu; Tanamal, Rinabi (Universitas Bunda Mulia, 2024)
This study aims to determine the effect of Shopee Live Streaming Features, Collaboration Branding, Brand Ambassadors, and Trust on Purchasing Decisions in the Shopee application. The sample of this study is Generation Z who uses the Shopee e-commerce application in Surabaya City with a total observation of 193 respondents. This study used a questionnaire as a data collection technique. The analysis model used is a structural equation model (SEM-PLS) with the help of SMART-PLS software. The results of data processing state that the variables Shopee Live Streaming, Collaboration Branding, Brand Ambassador, and Trust have a significant positive effect on Purchasing Decisions at Shopee E-Commerce. Based on the results of the F Square test, it can be concluded that the Trust variable is classified as having the most influential value on Purchasing Decisions.